PATEN DAN KOSMOPOLITANISME ISLAM: PROBLEMATIKA DI PERGURUAN TINGGI ISLAM - Hidayati, Tri (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Patent law serves as an innovative research stimulant, provides exclusive legal protection for inventors and encourages the use of science and technology in order to support the transformation of the national growth into International competitive one. It is relevant to the cosmopolitan Islamic concept. However, data shows there is only one patent right (until 2018) of Islamic universities in Indonesia. This social legal studies used the statute and historical approach explores the obstacles in the development of patent-based research results at Islamic Universities in Central Kalimantan. Internal constraints are: knowledge and understanding of patents are limited; pragmatism in research purposes; projections of research output are not systematic and unclear; and budgeting is not right. An external obstacles are no socialization of patent-based research rules; policies in the field of research have not been specifically oriented towards output patents; there has been no measurement of technological readiness level (TKT); limited research cost budget, and patent registration fees are considered expensive and have difficulty finding third parties as partners in running patents. Keywords: Patent law, Islamic cosmopolitanism, Islamic university